2018
DOI: 10.1016/j.jhin.2017.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Intensive care unit (ICU)-acquired bacteraemia and ICU mortality and discharge: addressing time-varying confounding using appropriate methodology

Abstract: In this study, even after adjusting for the timing of acquiring bacteraemia and time-varying confounding using inverse probability weighting for marginal structural models, ICU-acquired bacteraemia was associated with a decreased daily ICU discharge risk and an increased risk of ICU mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 25 publications
(40 reference statements)
1
23
2
Order By: Relevance
“…When it comes to risk factors for increased mortality in patients who acquired a HAI, intubation (OR = 6.7, P < .001) and diabetes mellitus (OR = 2.5, P = .042) were extracted as significant. Surprisingly, mechanical ventilation, which is often identified as a risk factor for HAI mortality, 24 was not identified together with intubation as a predictor in the multivariate analysis. Another interesting finding was the absence of MDR pathogens among risk factors for HAI mortality, since many studies have identified MDR/XDR strains to cause more severe infections with higher mortality rates, 25 while incurring higher hospital costs.…”
Section: Discussionmentioning
confidence: 83%
“…When it comes to risk factors for increased mortality in patients who acquired a HAI, intubation (OR = 6.7, P < .001) and diabetes mellitus (OR = 2.5, P = .042) were extracted as significant. Surprisingly, mechanical ventilation, which is often identified as a risk factor for HAI mortality, 24 was not identified together with intubation as a predictor in the multivariate analysis. Another interesting finding was the absence of MDR pathogens among risk factors for HAI mortality, since many studies have identified MDR/XDR strains to cause more severe infections with higher mortality rates, 25 while incurring higher hospital costs.…”
Section: Discussionmentioning
confidence: 83%
“…Many studies suffer from methodological shortcomings that may either underestimate or overestimate of the actual cost of ABR, as has been pointed out previously [14,17,23]. These shortcomings include (1) unmeasured baseline confounding (not adjusting for differences in the characteristics of patients with antibiotic-resistant, antibiotic-susceptible or no infection that affect their clinical outcomes or treatment costs), (2) time-dependent confounding (patients with antibiotic-resistant, antibiotic-susceptible or no infections have different changes to their characteristics such as health between the time of admission and acquiring an infection) [24,25], (3) time-dependent bias (patients with longer stays being more likely to acquire antibiotic-resistant infections) [25], and (4) model misspecification (use of inappropriate models to relate variables to outcomes, such as the use of Cox regression models even though the proportional hazards assumption is rarely valid for cost outcomes) [26]. The literature in this area has shown methodological improvements over time, with greater use of techniques that can correct for time-dependent biases, such as survival models incorporating infection as a time-dependent predictor and multi-state models [29].…”
Section: Hospital-based Studiesmentioning
confidence: 98%
“…The literature in this area has shown methodological improvements over time, with greater use of techniques that can correct for time-dependent biases, such as survival models incorporating infection as a time-dependent predictor and multi-state models [29]. However, few studies adjust for potential time-varying confounding when focusing on hospital-acquired cases, using g-methods such as marginal structural models with inverse probability weighting [25] or nested g-formulae [24]. In contrast to standard regression methods and multistate models, gmethods can provide unbiased estimates of an exposure if there is time-varying confounding that is also affected by the exposure, provided that confounding is accurately measured.…”
Section: Hospital-based Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed description of this procedure is provided in the tutorial by Therneau, Crowson, and Atkinson () and the Appendix of Pouwels et al. (). To obtain appropriate CIs, we propose to use a bootstrap method.…”
Section: A Counterfactual Approach To Define the Population‐attributamentioning
confidence: 99%